Statistics and Analysis of some Heavy Elements and Water Wells in the Suction of Babylon 2021 (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
This study has been performed at the (hila city, kefal, Nile, abi karaka) region to indicate the suitability of the ground water which is important source for civil uses. The sample taken from (125) wells which             IN this, study the concentration of rare heavy elements of the Ground water sample of (17) wells dug for selected wells from ( Hilla  , kefal , Nile , and abi karaka )  which included (Pb ,CU , NI , Cd , Fe , ZN ) for three seasons of May 2018 different concentration and study the factors affecting them it was found that the increase concentrations of this elements in residential areas and less in the agricultural areas and found that it is not polluted ground water for the  study area and falls within the specification of Iraqi and the world .